The Effectiveness of Islamic Spirituality Training on Academic Well-Being, Achievement Motivation, and Academic Affect - Bamari , Moslem; Rashidizadeh , Zeynab; Elahi, Mohammad (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to investigate the effectiveness of Islamic spirituality training on academic well-being, achievement motivation, and academic affect among high school students in Tehran. This study employed a quasi-experimental design with pretest, posttest, and follow-up stages using a control group. The statistical population consisted of high school students in Tehran during the 2025–2026 academic year. A total of 48 students were selected through purposive sampling and randomly assigned into an experimental group (n = 24) and a control group (n = 24). The experimental group participated in eight weekly sessions of Islamic spirituality training, each lasting 90 minutes, while the control group received no intervention. Data collection instruments included the Academic Well-Being Questionnaire, the Hermans Achievement Motivation Questionnaire, and the Academic Affect Scale. Data were analyzed using repeated-measures analysis of variance and Bonferroni post-hoc tests in SPSS-27 software. The results of repeated-measures analysis of variance indicated that Islamic spirituality training had a significant effect on academic well-being (F = 60.41, p = 0.001, η² = 0.57), achievement motivation (F = 55.92, p = 0.001, η² = 0.55), and academic affect (F = 65.12, p = 0.001, η² = 0.60). Bonferroni post-hoc comparisons demonstrated significant differences between pretest and posttest scores as well as between pretest and follow-up scores in the experimental group across all variables (p = 0.001). The findings showed that students who participated in the Islamic spirituality training program experienced increased academic well-being, stronger achievement motivation, and more positive academic affect compared to the control group, and these improvements remained relatively stable during the follow-up stage. The findings suggest that Islamic spirituality training is an effective educational and psychological intervention for improving students’ academic well-being, achievement motivation, and academic affect.